Kesan Penambahan Air Dalam Reaktor Haba Bermangkin Bagi Penyingkiran Tar Gas Pengeluar - Dahlani, Warsita (2016)
Tar in biomass producer gas should be removed to avoid blocking of the pipe lines and to allow producer gas utilization in internal combustion (IC) engines and turbines for power generation. Among the available tar removal methods, thermal and catalytic (thermocatalytic) treatments of tar are more attractive with improvement of the producer gas energy content by converting tar into combustible gases. The alternative method by using microwave heating and water addition is cost effective, clean energy source, simple and potential for process scale up. A modified commercial microwave oven was developed and characterized for thermocatalytic treatment of tar. Tar removal was conducted initially using tar model compounds (toluene and naphthalene) followed by real tar from producer gas derived from biomass gasification. Tar species and gases were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Thermal Conductivity Detector (GC-TCD), respectively.The experimental results showed that thermal heating process under low energy consumption of microwave irradiation is suitable for thermocatalytic treatment of tar. For tar model, about 95% of both toluene and naphthalene were removed during thermal treatment at temperatures of 10500C and 12000C, respectively. In catalytic treatment, about 99% toluene and 97% naphthalene were removed using dolomite at 8500C and 9000C respectively, whereas about 97% toluene and 95% naphthalene were removed using Yzeolite at 7000C. Further in the treatment of nickel 99% toluene and 97% naphthalene, while ruthenium was found to be 99% and 96%, while the last treatment with rhodium has eliminated 96% toluene and 95% naphthalene.